Chiral oxazolidinones as electrophiles: Intramolecular cyclization reactions with carbanions and preparation of functionalized lactams - Gibson, Sarah (2011)
The intramolecular cyclizations of oxazolidinones with carbanions adjacent to sulfones, sulfoxides and phosphonates proceed in high yields to obtain functionalized γ and δ lactams. The chiral oxazolidinone precursors can be readily synthesized from commercial amino acids. The lactams from this study are useful synthetic intermediates, as demonstrated by the synthesis of a precursor for levetiracetam, an antiepileptic drug.